Herpes simplex virus-1 entrapped in Candida albicans biofilm displays decreased sensitivity to antivirals and UVA1 laser treatment - Cristian Ascione; Arianna Sala; Elham Mazaheri-Tehrani; Simona Paulone; Beniamino Palmieri; Elisabetta Blasi; Claudio Cermelli (BMC, 2017)
Abstract Background Recently, we published data suggesting a mutualistic relationship between HSV-1 and Candida. albicans; in particular: (a) HSV-1 infected macrophages are inhibited in their anti-Candida effector function and (b) Candida biofilm protects HSV-1 from inactivation. The present in vitro study is aimed at testing the effects of Candida biofilm on HSV-1 sensitivity to pharmacological and physical stress, such as antiviral drugs (acyclovir and foscarnet) and laser UVA1 irradiation. We also investigated whether fungus growth pattern, either sessile or planktonic, influences HSV-1 sensitivity to antivirals. Methods Mature Candida biofilms were exposed to HSV-1 and then irradiated with laser light (UVA1, 355 λ). In another set of experiments, mature Candida biofilm were co-cultured with HSV-1 infected VERO cells in the presence of different concentrations of acyclovir or foscarnet. In both protocols, controls unexposed to laser or drugs were included. The viral yield of treated and untreated samples was evaluated by end-point titration. To evaluate whether this protective effect might occur in relation with a different growth pattern, HSV-1 infected cells were co-cultured with either sessile or planktonic forms of Candida and then assessed for susceptibility to antiviral drugs. Results UVA1 irradiation caused a 2 Log reduction of virus yield in the control cultures whereas the reduction was only 1 Log with Candida biofilm, regardless to the laser dose applied to the experimental samples (50 or 100 J/cm2). The presence of biofilm increased the IC90 from 18.4-25.6 J/cm2. Acyclovir caused a 2.3 Log reduction of virus yield in the control cultures whereas with Candida biofilm the reduction was only 0.5 Log; foscarnet determined a reduction of 1.4 Log in the controls and 0.2 Log in biofilm cultures. Consequently, the ICs50 for acyclovir and foscarnet increased by 4- and 12-folds, respectively, compared to controls. When HSV-1 was exposed to either sessile or planktonic fungal cells, the antiviral treatments caused approximately the same weak reduction of virus yield. Conclusions These data demonstrate that: (1) HSV-1 encompassed in Candida biofilm is protected from inactivation by physical (laser) and pharmacological (acyclovir or foscarnet) treatments; (2) the drug antiviral activity is reduced at a similar extent for both sessile or planktonic Candida.